Ultrafast charge carrier and exciton dynamics in an excitonic insulator probed by time-resolved photoemission spectroscopy. Issue 4 (December 2022) - Mor, Selene; Herzog, Marc; Monney, Claude; Stähler, Julia
Abstract: An excitonic insulator phase is expected to arise from the spontaneous formation of electron–hole pairs (excitons) in semiconductors where the exciton binding energy exceeds the size of the electronic band gap. At low temperature, these ground state excitons stabilize a new phase by condensing at lower energy than the electrons at the valence band top, thereby widening the electronic band gap. The envisioned opportunity to explore many-boson phenomena in an excitonic insulator system is triggering a very active debate on how ground state excitons can be experimentally evidenced. Here, we employ a nonequilibrium approach to spectrally disentangle the photoinduced dynamics of an exciton condensate from the entwined signature of the valence band electrons. By means of time- and angle-resolved photoemission spectroscopy of the occupied and unoccupied electronic states, we follow the complementary dynamics of conduction and valence band electrons in the photoexcited low-temperature phase of Ta2 NiSe5, the hitherto most promising single-crystal candidate to undergo a semiconductor-to-excitonic-insulator phase transition. The photoexcited conduction electrons are found to relax within less than 1 ps. Their relaxation time is inversely proportional to their excess energy, a dependence that we attribute to the reduced screening of Coulomb interaction and the low dimensionality of Ta2 NiSe5 . Long after ( > 10 ps) the conduction band has emptied, the photoemission intensity below the Fermi energy has not fully recovered the equilibrium value. Notably, this seeming carrier imbalance cannot be rationalized simply by the relaxation of photoexcited electrons and holes across the semiconductor band gap. Rather, a rate equation model involving different photoemission crosssections of the valence electrons and the condensed excitons is able to reproduce the delayed recovery of the photoemission intensity below the Fermi energy. The model shows that electron quantum tunnelling between the exciton condensate and the valence band top is enabled by an extremely small activation energy of 4 × 10 - 6 eV and explains the retarded recovery of the exciton condensate. Our findings not only determine the energy gain of ground state exciton formation with exceptional energy resolution, but also demonstrate the use of time-resolved photoemission to unveil the re-formation dynamics of an exciton condensate with femtosecond time resolution.